CONSUMER PERCEPTION AND ETHICS OF AI INFLUENCERS IN BANK BCA’S DIGITAL SECURITY CAMPAIGN - Andry Mochamad Ramdan (Journal of Golden Generation Economic, 2025)
The rapid advancement of Artificial Intelligence (AI) introduced Virtual Influencers (VIs) as innovative digital marketing tools, yet their adoption in high-trust sectors like banking presented unique challenges. This study analyzed the potential impact of using VIs on consumer perception and marketing ethics within the context of digital security campaigns. A qualitative-contextual approach was employed, examining Bank Central Asia’s (BCA) “Don’t Know? Kasih No!” (DKKN) campaign as a primary case study. The research explored the implications of replacing a highly credible human figure, Indro Warkop, with a VI. Drawing on Source Credibility, Parasocial Relationship, and Marketing 6.0 theories, the analysis identified an inherent trust deficit in VIs. Results indicated that while the actual DKKN campaign successfully garnered over 100 million views and reduced customer financial losses by 41%, a hypothetical AI-led version would likely trigger consumer skepticism due to a lack of experiential authenticity. Furthermore, an ethical paradox was discovered where mandated AI transparency disclosure triggered skepticism among Gen Z users. It was concluded that for high-stakes financial communication, human influencers remained superior due to their emotional relatability and the "sentience factor" required for cybersecurity advocacy. This paper recommends that banking institutions limit VIs to functional roles rather than high-stakes security literacy.